How to be secular : a call to arms for religious freedom - Berlinerblau, Jacques (Boston : Houghton Mifflin Harcourt, 2012)
Argues that a return to a more secular America will promote religious diversity and freedom, and help eliminate the widening divide between religious conservatives and staunch atheists.
What secularism is and isn't : What is secularism? (the basic package) ; Were the founders secular? ; Does secularism equal total separation of church and state? ; Does secularism equal atheism? ; How not to be secular -- The very peculiar "rise" and fall of American secularism : The "rise" of American secularism and the secularish ; The fall of American secularism ; Are Democrats secularists? ; The Christian nation and the GOP -- Reviving American secularism : Who could be a secularist? ; How to be secularish (in praise of "secular Jews" and "cafeteria Catholics") ; Tough love for American secularism.
Includes bibliographical references (pages 212-290) and index.
Keywords: Secularism -- United States; Freedom of religion -- United States; United States -- Religion; Church and state -- United States